Fe-zeolite catalyst for ozonation of pulp and paper wastewater for sustainable water resources. (June 2022) - Munir, Hafiz Muhammad Shahzad; Feroze, Nadeem; Ramzan, Naveed; Sagir, Muhammad; Babar, Muhammad; Tahir, Muhammad Suleman; Shamshad, Jaweria; Mubashir, Muhammad; Khoo, Kuan Shiong
Abstract: The pulp and paper industry consumes enormous quality of freshwater, leading to wastewater. It must be treated to remove pollutants, particularly residual dyestuffs, before releasing them to water bodies to avoid adverse environmental effects. The traditional wastewater treatment methods used for the pulp and paper industry are less efficient in colour and chemical oxygen demand (COD) removal. The current study is aimed at developing a novel catalyst for the catalytic ozonation of pulp and paper wastewater with better colour and COD removal for sustainable resources of clean water. The proposed catalyst is impregnated by iron on natural zeolites. Various parameters such as catalyst dose, pH, ozone dose, initial COD concentration, and reaction time are studied and optimized. The performance was evaluated by comparing the results with the single ozonation process (SOP) and catalytic ozonation process (COP). The highest COD and colour reduction efficiencies have been achieved, i.e., 71%, and 88% at a natural pH of 6.8. The proposed process achieved higher COD and colour efficiencies than the single ozonation process and catalytic ozonation process using raw zeolites. The improvement in efficiencies are 23% and 29% for SOP and 17% and 19% for COP, respectively. Hence, the results proposed the sustainability and applicability of COP to treat paper and pulp sector effluent. Graphical abstract: Image 1 Highlights: A novel Fe-zeolite catalyst was developed for catalytic ozonation process. Performance of single ozonation process and catalytic ozonation process was evaluated. Under optimized condition the catalyst remains efficient even after 5 cycles. 71% of COD were eliminated using Fe/NZ as catalyst in catalytic ozonation process. The optimum ozone dose for COD and color removal was 0.3 mg/ml of wastewater.